Enhancement of Food Waste Management and Its Environmental Consequences - Jan den Boer; Gudrun Obersteiner; Sebastian Gollnow; Emilia den Boer; Renata Bodnárné Sándor (Energies, 2021)
This paper assesses the potential environmental effects of the optimization of the kitchen waste management in Opole. The separate collection of kitchen waste is improved by distribution of separate collection kits consisting of an in-home bin and 10 L biodegradable bags. The surplus of collected kitchen waste is diverted from treatment in a mechanical-biological pretreatment (MBP) along with the residual waste to anaerobic digestion (AD) with the biowaste. This has positive effects on European and Polish goals, ambitions, and targets, such as (i) increasing the level of renewables in the primary energy supply, (ii) decreasing the level of greenhouse gas (GHG) emissions, (iii) increasing the level of preparation for reuse and recycling of municipal waste. The environmental effects of 1 ton additionally separately collected and treated kitchen waste are determined by using life cycle assessment. It was shown that in all selected impact categories (global warming potential, marine eutrophication potential, acidification potential, and ozone depletion potential) a clear environmental benefit can be achieved. These benefits are mainly caused by the avoided emissions of electricity and heat from the Polish production mix, which are substituted by energy generation from biogas combustion. Optimization of the waste management system by diversion of kitchen waste from mechanical-biological pretreatment to anaerobic digestion can lead to considerable saving of 448 kg CO2-eq/t of waste diverted. With an estimated optimization potential for the demonstration site of 40 kg/inh·year for the city of Opole, this would lead to 680,000 t CO2-eq savings per year for the whole of Poland. The sensitivity analysis showed that with a choice for cleaner energy sources the results would, albeit lower, show a significant savings potential.